2018
DOI: 10.1371/journal.pone.0194713
|View full text |Cite
|
Sign up to set email alerts
|

Predicting short-term interruptions of antiretroviral therapy from summary adherence data: Development and test of a probability model

Abstract: Antiretroviral therapy (ART) for HIV is vulnerable to unplanned treatment interruptions–consecutively missed doses over a series of days–which can result in virologic rebound. Yet clinicians lack a simple, valid method for estimating the risk of interruptions. If the likelihood of ART interruption could be derived from a convenient-to-gather summary measure of medication adherence, it might be a valuable tool for both clinical decision-making and research. We constructed an a priori probability model of ART in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Flag patients early for intervention [ 57 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Flag patients early for intervention [ 57 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 ]…”
Section: Resultsmentioning
confidence: 99%
“…While VL is considered the gold standard for monitoring treatment response [ 50 ], the mixed evidence means no measure perfectly reflects successful engagement or its dimensions. Measures are chosen to prioritize sensitivity or specificity in predicting outcomes, resulting in a trade‐off between missing people in need of support or over‐intervening and wasting resources [ 125 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that observed frequencies of runs of ≥3 and ≥4 consecutively missed doses were significantly greater than expected from random chance. In a similar approach, Harris et al 20 compared the observed and calculated distributions of ≥3 consecutively missed doses of an antiretroviral drug regimen. ( Figure 1 in the study by Harris et al, 20 comparing the observed and theoretical distributions of ≥3 consecutively missed doses in 185 patients over a period of 90 days, is the formal equivalent of Figure 2 , middle panel in the present work.)…”
Section: Discussionmentioning
confidence: 99%
“…In a similar approach, Harris et al 20 compared the observed and calculated distributions of ≥3 consecutively missed doses of an antiretroviral drug regimen. ( Figure 1 in the study by Harris et al, 20 comparing the observed and theoretical distributions of ≥3 consecutively missed doses in 185 patients over a period of 90 days, is the formal equivalent of Figure 2 , middle panel in the present work.) In the study by Harris et al, the observed frequencies of ≥3 consecutively missed doses were statistically significantly higher than the calculated random probabilities at levels of average adherence of 0.85–0.97, corresponding to between 1 and 4–5 missed doses in a 30-day period, whereas there was no statistically significant difference between the observed and calculated frequencies at levels of average adherence of 0.40 to <0.85, corresponding to 4–5 to 18 missed doses in a 30-day period.…”
Section: Discussionmentioning
confidence: 99%